Renewable energy consumption and unemployment: evidence from a sample of 80 countries and nonlinear estimates - Apergis, Nicholas; Salim, Ruhul (Routledge, 2015)
This article contributes to the discussion on the dynamic nexus of renewable energy consumption and unemployment by incorporating nonlinear cointegration and causality analysis. Using a sample of 80 countries spanning the period 1990–2013 and the advanced generation of unit root, cointegration and nonlinear Granger causality methodological approaches in panel data, we obtain mixed results about the impact of renewable energy consumption on unemployment. Although the total findings document a positive impact of renewable energy consumption on unemployment, disaggregated data across specific regions, such as Asia and Latin America, highlight the favourable effect on unemployment, implying that the effect of renewable energy consumption on jobs creation depends on the cost of adopting renewable energy technologies and energy efficiencies that seem to vary across the regions under investigation.